Pool boiling characteristics of microalgae suspension for biofuels production - Zeng, X.; Quek, C.; Danquah, Michael; Woo, M.; Chen, X.; Lu, Y. (2013)
The use of microalgae for biofuels and other microalgal sourced products has received significant interests in recent years. Dewatering is a major obstruction in industrial-scale processing microalgae suspensions. Basically, the dilute nature of the harvested microalgal cultures leads to a considerable operational cost during dewatering, thereby rendering algae-based products less economically attractive. Evaporation, which is used widely in industry, dominates in concentrating temperature sensitive products processing. In order to explore the possibility of evaporation as a credible option in microalgae suspension dewatering, basic engineering information is needed. In this work, microalgae suspension characteristics and rheological properties have been investigated. Moreover, pool boiling under vacuum has been tested to establish the relevant heat and mass transfer characteristics. The corresponding Nu-Reb correlations have been obtained for the evaporative heat transfer process. It is probably the first time that a study has been focused on microalgae culture dewatering using an evaporation means. © 2012 Elsevier Ltd. All rights reserved.